Electrical system load re-phasing: a case of a university building in the Philippines - Marcos, Ferdinand L.; Domingo, Enalyn T.; Lapuz, Cid L. (Institute of Advanced Engineering and Science, 2025)
In the pursuit of attaining energy efficiency, administrators must delve deeply into the electrical system of a facility, especially if it is an old structure. As years go by, renovations and the addition of new equipment may lead to an imbalance in the electrical system. These imbalances may lead to inefficiencies, contributing to damage to equipment. This study aimed to investigate the electrical system of a university building by determining whether the percent current and voltage unbalance values in the system meet the standards. For non-conforming electrical branches, re-phasing schemes were proposed. Data revealed that the majority of the panelboards in the building have voltage imbalances that are within the allowable limit, while there is a considerable number of panelboards with above-the-minimum current unbalance value. The original configurations of some panelboards were retained to avoid further increase in the percentage of current imbalance associated with re-phasing. Merging certain panelboards, however, resulted in a reduction of current imbalances within the acceptable limit. If the re-phasing and merging of loads are to be implemented, a cost-benefit analysis and a study on the improvements in energy efficiency may be considered for further research.